Aplikasi pupuk organik cair limbah kulit ari kedelai terhadap pertumbuhan dan produksi Pakcoy (Brassica rapa L.) - Munarti, Munarti; Kurniasih, Surti; Prasaja, Dimas; Kurniawan, Ahmad (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: Soybean husk is waste from the tempe making process which contains organic materials and nutrients so that it can be used as raw material for making organic fertilizer. The use of organic fertilizer on vegetable plants is one effort to meet the need for organic vegetables. This research aims to obtain information on the nutrient and heavy metal content of liquid organic fertilizer for soybean epidermis and the effect of this fertilizer on the growth and yield of pak choy. This research was carried out in December 2022-July 2023, in Citeureup, Bogor and the Laboratory of the Faculty of Agriculture, IPB University. The experimental design used was a Randomized Block Design with three replications. The liquid organic fertilizer treatments used consisted of control, 5%, 10%, 15% and 20%. The parameters observed were plant height, number of leaves, leaf area and plant wet weight. The results showed that liquid organic fertilizer from soybean epidermis contained C-organic (1.63%), C/N ratio (20.13), macro nutrients (N+P₂O₅ +K₂O) 0.42%, total and available Fe (26.61ppm and 25.56 ppm) and Zn (0.42ppm). The heavy metal content (Pb, Cd, Cr, As, Hg) meets the quality standards set by the Minister of Agriculture of the Republic of Indonesia No. 261 of 2019, so that it can be applied to plants. Liquid organic fertilizer with a concentration of 5% was the best supporting growth and production of Pak Choy compared to the control, 10%, 15% and 20%.